2017
DOI: 10.1007/s11095-017-2256-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation Pathways of Protein Disulfides: Human Growth Hormone

Abstract: A comprehensive analysis of photodegradation products revealed a variety of novel photo-products, including cross-links, originating from disulfide degradation. The mechanisms of product formation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…Disulfide scrambling induced by UV light exposure has also been observed in a monoclonal antibody and human growth hormone. 18,19 However, it has not previously been reported that photoproducts with a thioether can participate in scrambling due to the initial presence of free thiols from the other sulfur atom in the original disulfide group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disulfide scrambling induced by UV light exposure has also been observed in a monoclonal antibody and human growth hormone. 18,19 However, it has not previously been reported that photoproducts with a thioether can participate in scrambling due to the initial presence of free thiols from the other sulfur atom in the original disulfide group.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the dithiohemiacetal group upon photoexcitation of a disulfide bond has previously been identified in a 12 residue model peptide, IgG1 antibody, and human growth hormone. 18,41,42 This diversity in the molecular formats emphasizes that the photoconversion of the disulfide group to a dithiohemiacetal is not a molecule-specific photomodification but relies on fundamental reaction mechanisms induced by UV light. The photoreaction was proposed to be initiated by a direct photoexcitation of the disulfide group which dissociates to thiyl radicals (−S • ) that cause the atomic rearrangements.…”
Section: Resultsmentioning
confidence: 99%
“…A specific improvement for the resolution and detection of these modifications is the use of very long columns (!1m), coupled to mass spectrometry detection. 164,165…”
Section: Biological Oxidation Of Protein Therapeuticsmentioning
confidence: 99%
“…While many more spontaneous reactions of amino-acid residues are known than those mentioned, like reversible hydrogen-transfer reactions involving thiyl radicals in Cys-containing peptides and proteins (Mozziconacci et al 2010(Mozziconacci et al , 2011Steinmann et al 2017), still many others are expected to occur, which will need to be detected and explored both mechanistically and biologically (Schöneich 2017). Future research in this field will enormously support the development of safe and potent peptide and protein drugs.…”
Section: Discussionmentioning
confidence: 99%